On the Image of Jews in Latin Humanist Poetry - Jana Kolářová (Slovo a Smysl, 2022)
This study is devoted to the depiction of Jews, Jewishness and the stereotypes connected therewith in Latin humanist poetry (from approximately the first third of the 16th century to the beginning of the 17th century). An analysis of the texts of ‘occasional poetry’ confirmed the predominant antiJewish discourse which pervaded the intellectual circles to whom the authors of this poetry mostly belonged during the time of Renaissance humanism.